Management of prolonged second stage of labor - Singh, Sanjay; Kohli, Uttara Aiyer; Vardhan, Shakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Second stage of labour has been often neglected leading to increased maternal and perinatal morbidity. Recognising and managing prolonged second stage is a challenge even to an experienced obstetrician. This article reviews the changes in the definition of prolonged second stage over the years. It discusses the causes, recognition and management options along with the difficulties in delivering a patient with prolonged second stage of labour. Though adding an extra hour to the definition of second stage in patients may reduce the rate of caesarean section but some studies also show a rise in maternal and perinatal morbidity. Obstetricians are familiarized to the different techniques of delivery of the impacted head. Once diagnosis of prolonged second stage is confirmed, causes should be identified and addressed, and treatment should be individualised, and timing and mode of intervention planned.